2001
DOI: 10.1042/bj3560217
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of murine ferrochelatase glutamate-287 with glutamine or alanine leads to porphyrin substrate-bound variants

Abstract: Ferrochelatase (EC 4.99.1.1) is the terminal enzyme of the haem biosynthetic pathway and catalyses iron chelation into the protoporphyrin IX ring. Glutamate-287 (E287) of murine mature ferrochelatase is a conserved residue in all known sequences of ferrochelatase, is present at the active site of the enzyme, as inferred from the Bacillus subtilis ferrochelatase threedimensional structure, and is critical for enzyme activity. Substitution of E287 with either glutamine (Q) or alanine (A) yielded variants with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…This behavior requires that significant amounts of the EZnD IX complex exist in the steady state and therefore that ZnD IX disassociation is partially rate-limiting. This result is thus in agreement with previous transient kinetic studies using iron (16) and zinc (33,34) as metal ion substrates. This conclusion can be contrasted to previous work with the bovine enzyme (35) where steady-state inhibition studies using both product and alternative substrate demonstrated an ordered mechanism where iron bound first.…”
Section: Discussionsupporting
confidence: 83%
“…This behavior requires that significant amounts of the EZnD IX complex exist in the steady state and therefore that ZnD IX disassociation is partially rate-limiting. This result is thus in agreement with previous transient kinetic studies using iron (16) and zinc (33,34) as metal ion substrates. This conclusion can be contrasted to previous work with the bovine enzyme (35) where steady-state inhibition studies using both product and alternative substrate demonstrated an ordered mechanism where iron bound first.…”
Section: Discussionsupporting
confidence: 83%
“…In the wild-type model, the N-terminal loop residues Gln 248 and Ser 249 were buried deeply inside the active site cavity and in very close proximity (about 4 Å) to His 209 and Glu 289 , which were proposed to be essential for catalysis (31)(32)(33)(34). Lys 250 was solvent-exposed, with the side chain projecting to the protein exterior and in close contact with the Gln 260 residue.…”
Section: Purification and Steady-state Kinetic Analysis Of Wild-type mentioning
confidence: 99%
“…1, 2,3), but there are very few reports of transient kinetics (3,27). Most functional analysis and assessment of the significance of mutated residues has relied on steady-state information.…”
mentioning
confidence: 99%